1998
DOI: 10.1143/jjap.37.l465
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Pt Bottom Electrodes for Ferroelectric Capacitors

Abstract: The stress of Pt films deposited at various temperatures and its correlation with the formation of hillocks during heat treatment were investigated. The residual stress changes from compressive to tensile as the deposition temperature increases. The compressive residual stress of a Pt film deposited at room temperature is initially relaxed by the shrinkage of the film thickness and then by hillock formation at a certain maximum compressive stress when the Pt film is heat-treated. On the other hand, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…As previously reported, Pt films made at low temperatures are under compressive stress, 12,15 whereas the ones deposited at high temperature are under tensile stress after cooling due to the larger thermal expansion coefficient for Pt compared to the one for the substrate (8.8 × 10 −6 and 2.6 × 10 −6 K −1 at room temperature, respectively). 16 For the deposition conditions used in this study, Pt films made at 200 • C should be under compressive or low tensile stress whereas the ones deposited at 500 • C are under tensile stress.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…As previously reported, Pt films made at low temperatures are under compressive stress, 12,15 whereas the ones deposited at high temperature are under tensile stress after cooling due to the larger thermal expansion coefficient for Pt compared to the one for the substrate (8.8 × 10 −6 and 2.6 × 10 −6 K −1 at room temperature, respectively). 16 For the deposition conditions used in this study, Pt films made at 200 • C should be under compressive or low tensile stress whereas the ones deposited at 500 • C are under tensile stress.…”
Section: Resultsmentioning
confidence: 69%
“…The adhesion layers used at the interface between SiO 2 and Pt and the platinum deposition conditions also play a key role in the final properties of the capacitors due to the diffusion processes and/or changes in the stress state of the platinum electrodes. [11][12][13][14] As previously reported, different metals like Ti, Zr, Ta, Ru and their oxides have been used as buffer layers. Maeder et al demonstrated that zirconium has a very good adhesion to both silica and platinum and excellent barrier layer properties for both lead and silicon diffusion but no ferroelectric properties of PZT thin films were investigated using Zr adhesion layers.…”
Section: Introductionmentioning
confidence: 97%
“…[8][9][10] For Pt films deposited using dc sputtering at low temperatures, a compressive stress is generally present. 10,[18][19][20] The stress is relaxed under high-temperature treatments through the formation of Pt hillocks and becomes tensile upon cooling down to room temperature because of the thermal strain. 8,19,20 That is the case for the unannealed Pt/ TiO x electrode in the present study.…”
Section: A Formation Of Pt Hillocks On the Bare Pt Electrodementioning
confidence: 99%
“…10,[18][19][20] The stress is relaxed under high-temperature treatments through the formation of Pt hillocks and becomes tensile upon cooling down to room temperature because of the thermal strain. 8,19,20 That is the case for the unannealed Pt/ TiO x electrode in the present study. However, the population and size of the Pt hillocks increase upon the further thermal annealing, which strongly suggests the generation of a compressive stress during the annealing.…”
Section: A Formation Of Pt Hillocks On the Bare Pt Electrodementioning
confidence: 99%
“…For ferroelectric capacitors, platinum is a widely used electrode material because of its good thermal and chemical stability [3]. Usually, ferroelectric capacitors are fabricated after the completion of basic CMOS processes except for the Al metallization.…”
Section: Introductionmentioning
confidence: 99%